The Effect of Online Learning on Mathematics Learning Achievement in Elementary School Students - Norkholizah Norkholizah; Danuri Danuri; Hermanto Hermanto (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study is to measure the average percentage of mathematics learning achievement of fifth-grade students when online learning was implemented and its impact when face-to-face learning was limited. The population in this study was 150 fifth-grade students in Tanah Bumbu Regency with the type of ex-post fact research. The data collection technique was in the form of a test technique and a psychological scale in the form of an instrument with a simple linear regression analysis technique. Test requirements analysis to test the hypothesis using a simple regression test. Before the simple regression test, prerequisite tests were carried out in the form of normality test, linearity test, and heteroscedasticity test. Based on the research results, it is known that online learning partially has a significant effect of 3.6% on learning achievement in Mathematics. However, it is known that when applied face-to-face learning was limited, students had not fully mastered the previous material and the subject matter being studied.